Influence Perineal Massage and Breathing Techniques for Reducing Perineal Trauma During Childbirth - Karuniriati , Tyas Alfi; Kundarti, Finta Isti; Yuswanto, Tri Johan Agus; Triningsih, Reni Wahyu (Program Studi S1 Kebidanan - Fakultas Ilmu Kesehatan Universitas PGRI Adi Buana Surabaya, 2025)
Perineal trauma is a common complication in primigravida women during vaginal childbirth, leading to pain, infection, and psychological distress. Non-pharmacological methods like perineal massage and deep breathing techniques may help reduce such trauma. This study employed a true experimental posttest-only control group design, involving 62 primigravida women who were randomly divided into an intervention group (n=31) and a control group (n=31). Conducted in Malang Regency in July 2025, the intervention included perineal massage starting at 34 weeks of gestation, done twice a week for 10 minutes using lubricant, and deep breathing techniques during contractions and pushing. Data were analyzed using the Mann-Whitney U test. A significant difference was found between groups. The intervention group had a sum of ranks of 270.00, while the control group had 81.00 (p = 0.001), indicating a lower incidence of perineal trauma in the intervention group. Perineal massage combined with deep breathing techniques is a safe and effective non-pharmacological approach to reduce perineal trauma in primigravida women during childbirth.